An application of simulated Kalman filter optimization algorithm for parameter tuning in proportional-integral-derivative controllers for automatic voltage regulator system - Badaruddin, Muhammad; Pebrianti, Dwi; Normaniha, Abd Ghani; Nor Hidayati, Abdul Aziz; Nor Azlina, Ab Aziz; Mohd Saberi, Mohamad; Mohd Ibrahim, Shapiai; Zuwairie, Ibrahim (IEEE, 2018)
This paper reports the first attempt to tune gain values in proportional-integral-derivative (PID) controllers using an optimizer called simulated Kalman filter (SKF) algorithm. Compared to another well-established optimizer, such as particle swarm optimization (PSO), the SKF algorithm is a relatively new optimizer and most importantly, the SKF algorithm has not been applied to parameter tuning of PID controller. The findings suggest that the SKF algorithm has promising potentials to be a good tuning method in PID controller.